Ecranisation of Nizami Ganjavi’s Classical Narrative Poem Layla Majnun into Monty Tiwa’s Film Adaptation - Ulmi Asrah; Sitti Wahidah Masnani; Mujadilah; Andi Agussalim (PT. Global Research Collaboration, 2026)
This study examines the process of adapting Nizami Ganjavi's classic Persian narrative poem Layla Majnun into an adaptation film directed by Monty Tiwa (2021), with an emphasis on the ideological implications of the narrative transformation that occurs. Using a descriptive qualitative approach with comparative analysis techniques, this study analyzes changes in plot elements, characters, and settings. The results of the study show that the process of subtraction, addition, and variation is not just a technical strategy in adaptation, but functions as a mechanism of cultural domestication that fundamentally changes the meaning of love in stories. The omission of mystical and tragic elements such as the removal of the character of Nowfal and the change in the final story from death to happiness shows a shift from a theocentric and transcendental concept of love to an anthropocentric and realistic one. Thus, the film transforms an original allegorical-spiritual narrative into a contemporary romance discourse that emphasizes individual agency, emotional reality, and social relevance. This study confirms that ecranisation is a form of ideological reconstruction that allows classical values to be redefined according to the context and expectations of modern audiences.